2004
DOI: 10.1007/s00415-004-0305-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilateral subthalamic stimulation on sleep in Parkinson?s disease

Abstract: Chronic STN stimulation is associated with a sleep improvement, which can be explained in part by the concomitant decrease in motor disturbances but also by the reduction in dosages of antiparkinsonian medication. However, we can not exclude a direct effect of STN stimulation on sleep regulatory centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 16 publications
4
53
1
4
Order By: Relevance
“…3,4,5 To date, most studies including objective polysomnographic measures have been small case series, with different patient populations, study protocols, various assessment time points, and electrode settings: Arnulf and colleagues evaluated 10 insomniac PD patients 3 to 6 months after STN-DBS, and found stimulation to increase total sleep time and sleep efficiency. 6 Similar findings have been made by Monaca et al in 10 patients before STN-DBS and again after 3 months, 7 by Cicolin and colleagues in 5 patients before and 3 months after bilateral STN-DBS electrode implantation, 8 and by Merlino et al in 15 patients one week before and after microsubthalamotomy. 9 On the other hand, Iranzo and colleagues evaluated 11 PD patients before and 6 months after bilateral STN-DBS implantation, but stimulation did not increase sleep efficiency.…”
Section: Introductionsupporting
confidence: 73%
“…3,4,5 To date, most studies including objective polysomnographic measures have been small case series, with different patient populations, study protocols, various assessment time points, and electrode settings: Arnulf and colleagues evaluated 10 insomniac PD patients 3 to 6 months after STN-DBS, and found stimulation to increase total sleep time and sleep efficiency. 6 Similar findings have been made by Monaca et al in 10 patients before STN-DBS and again after 3 months, 7 by Cicolin and colleagues in 5 patients before and 3 months after bilateral STN-DBS electrode implantation, 8 and by Merlino et al in 15 patients one week before and after microsubthalamotomy. 9 On the other hand, Iranzo and colleagues evaluated 11 PD patients before and 6 months after bilateral STN-DBS implantation, but stimulation did not increase sleep efficiency.…”
Section: Introductionsupporting
confidence: 73%
“…They showed that stimulation significantly increased total sleep time and sleep efficiency and improved subjective sleep quality as well. In addition, the duration of slow wave sleep and REM sleep was increased, but the percentages of each sleep stage were not significantly different, and changes in sleep did not correlate significantly with motor improvement [Monaca et al 2004]. Cicolin and colleagues showed significantly reduced WASO, increased sleep efficiency, and decreased REM latency in five patients with PD 3 months after bilateral STN DBS.…”
Section: Subthalamic Nucleus Deep Brain Stimulationmentioning
confidence: 99%
“…Previous electrophysiological and patient-reported outcome-based studies demonstrated the beneficial effect of STN DBS on sleep quality in PD [3][4][5][6].…”
Section: Introductionmentioning
confidence: 97%